(untitled) (Anclajes, 2014)
Language usage is probably one of the most discussed issues in language scholarship, and undoubtedly a frequent cause of division among researchers on this field. The usage-question is also present in some instances of the language-ideological debates which took place in Latin America and Spain all along the 19th century and deep into the 20th. It reveals itself tightly bound to issues also related to this question in other areas, like property and law, allowing the research on what could be called a linguistic political economy, which rules and laws are being there subjected to debate. This paper proposes to begin the discussion by analyzing some crucial texts of Andrés Bello, Miguel Antonio Caro, Rufino José Cuervo and Rudolf Lenz, which can help to sketch the boundaries and scope of this issue.